Impact Assessment of Ration Balancing on Productive Performance and Economics of Milk Production in Field Conditions - Tomar, Divyanshu Singh; Lathwal, S.S.; Singh, Pawan; Devi, Indu (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
A field survey was conducted to assess the ration balancing programme undertaken by ICAR-NDRI on the extent of productivity increase and cost reduction on the adoption of balanced animal ration. Four villages were selected, out of which, two villages received services such as the provision of the mineral mixture from ICAR-NDRI and ration balancing programme under NDP-I was also implemented in these two villages (Treatment villages – Lalukheri and Alipur) and the other two villages didn’t receive any kind of services from the ICAR-NDRI (Control villages – Dhansaini and Bhoura-Khurd). From each village, about 50 dairy farmers were randomly selected. Data were collected on feeding management practices using a pre-tested interview schedule. The collected data was analyzed using propensity score matching to control bias due to confounding variables. Results revealed that more cattle and buffaloes were fed on a balanced ration in treatment villages as compared to control villages. Attributed to ration balancing the average daily milk yield of Murrah, HF and Jersey crossbreds was significantly increased by 25.7%, 18.8% and 37% (unmatched) respectively, and the quantum of increase after controlling for the confounding factors by calculation of average treatment on the treated resulted in an 8.8%, 9.3% and 13.4% increase in case of Murrah, HF and Jersey crossbreds, respectively. Fat% and SNF% were improved significantly (P < 0.01) only in Murrah buffaloes fed with balanced ration. Total feeding cost didn’t vary between RBP and non-RBP animals after the calculation of ATT. However, the cost of feed per kg of milk of the RBP animals was found to be around 15% significantly (P < 0.01) lower than the non-RBP animals. The total returns, net returns from milk production as well as the milk-feed ratio of RBP animals were significantly higher.